Answers

2016-07-13T20:09:19+08:00
  • Brainly User
2016-07-14T10:36:05+08:00
First number: x
Second Number: x + 1

Equation:

(x) (x+1) = 42

x² + x - 42 = 0

Since it is apparent that the numbers are 6 and 7, and most will use factoring because it is more convenient even without understanding the concept, I will use completing the square to solve the quadratic equation:

x² + x + (1/2)² = 42 + (1/2)²

(x + 1/2)² = 42 + (1/4)

(x + 1/2)² = 168/4 + 1/4

(x + 1/2)² = 169/4

 \sqrt{(x+ \frac{1}{2}) ^{2} }  \sqrt{ \frac{169}{4} }

x + 1/2 = +/-  13/2

x = - 1/2 + 13/2              x = -1/2 - 13/2

x =  - 1/2 + 13/2             x = -1/4 - 13/2

x = 12/2                         x = -14/2

x = 6                            x = -7

First number: x = 6
Second number: 6 + 1 = 7

ANSWER:  6 and 7


0